Promoting human wellness : new frontiers for research, practice, and policy - Jamner, Margaret Schneider; Stokols, Daniel (University of California Press, 2000)
This book is a state-of-the-art educational resource on the latest research and public-policy developments in the fields of wellness promotion and disease prevention. Based on award-winning lectures by University of California faculty on nine campuses as part of the Wellness Lectures Program jointly funded by The California Wellness Foundation, Health Net, and the University of California, the volume aims to widen the scope of health care research and policy to promote wellness rather than focus on illness and disease, and to incorporate proactive, interdisciplinary approaches to health care.